2005
DOI: 10.1002/ajmg.a.30570
|View full text |Cite
|
Sign up to set email alerts
|

X-linked dominant chondrodysplasia with platyspondyly, distinctive brachydactyly, hydrocephaly, and microphthalmia

Abstract: We describe a family with an X-linked dominant chondrodysplasia. Four males and six females were affected through four generations. Identification of skeletal abnormalities and hydrocephaly during the pregnancy of three male fetuses led to termination of the pregnancies. A fourth affected male died at 6 days of life. The four patients had chondrodysplasia, hydrocephaly, and facial features with microphthalmia. Radiographs showed severe platyspondyly and various bone abnormalities including a distinctive metaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Our data, supported by the known functions of HDAC6 and other HDACs, in particular HDAC4, another class II HDAC, strongly suggest that we have probably identified the molecular cause of the new form of X-linked chondrodysplasia that we previously described (2). This would represent to our knowledge the first example of a developmental disease caused by the abrogation of the post-transcriptional regulation normally exerted by a microRNA on its target gene.…”
Section: Discussionsupporting
confidence: 76%
“…Our data, supported by the known functions of HDAC6 and other HDACs, in particular HDAC4, another class II HDAC, strongly suggest that we have probably identified the molecular cause of the new form of X-linked chondrodysplasia that we previously described (2). This would represent to our knowledge the first example of a developmental disease caused by the abrogation of the post-transcriptional regulation normally exerted by a microRNA on its target gene.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, a hemizygous deletion of HDAC9 has been identified in a small proportion of schizophrenia patients [137]. Moreover, mutations in the 3′ untranslated regions (UTR) of HDAC6 , which encodes the class IIB KDAC enzyme, suppress miR433-mediated posttranscriptional regulation and cause overexpression of HDAC6 , resulting in chondrodysplasia with platyspondyly, distinctive brachydactyly, hydrocephaly, and microphtalmia syndrome (OMIM 300863), which exhibits, among other symptoms, hydrocephaly and macrocephaly [138], [139]. Taken together, these findings suggest an essential role of KDACs during brain development in humans and argue for distinct functions of different KDACs during this process.…”
Section: Human Disorders Caused By Abnormalities In Kat or Kdac Activitymentioning
confidence: 99%
“…Chondrodysplasia is caused by alterations in the extracellular matrix of the cartilage or defects in the differentiation and proliferation of chondrocytes. Chassaing et al (Chassaing et al 2005) reported a new form of X-linked dominant chondrodysplasia that is different from the other X-linked types of chondrodysplasia, such as CDPX1, CDPX2 and CHILD syndrome. Affected males exhibit severe phenotypes that include platyspondyly, hydrocephaly, facial dysmorphism and microphtalmia, whereas affected females show less severe phenotypes, namely small stature with variable expression of body asymmetry and mental retardation (Chassaing et al 2005).…”
Section: A Mutation In the Mir-433-binding Site Of The Hdac6 Gene Assmentioning
confidence: 99%
“…Chassaing et al (Chassaing et al 2005) reported a new form of X-linked dominant chondrodysplasia that is different from the other X-linked types of chondrodysplasia, such as CDPX1, CDPX2 and CHILD syndrome. Affected males exhibit severe phenotypes that include platyspondyly, hydrocephaly, facial dysmorphism and microphtalmia, whereas affected females show less severe phenotypes, namely small stature with variable expression of body asymmetry and mental retardation (Chassaing et al 2005). Subsequently, the same group identified an A-to-T mutation in the 3'UTR of the Histone deacetylase 6 (HDAC6) gene that is present in all the affected members of the family (Simon et al 2010).…”
Section: A Mutation In the Mir-433-binding Site Of The Hdac6 Gene Assmentioning
confidence: 99%